Transnational democracy : political spaces and border crossings - Anderson, James, 1941- (Transnationalism., 2002)
A multidisciplinary array of experts explore the issues related to globalisation and democracy. They focus on federalism, multi-cultural societies, the European Union and potential agents for the democratisation of global institutions.